SAT0091 INCREASED FREQUENCY AND DEFECTIVE SUPPRESIVE CAPACITY OF CD4+CD25+FOXP3+ TREG CELLS IN CHINESE PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - He, Lan; Ju, Bomiao; Zhang, Jing; Hu, Nan; Zhu, LI; Zheng, Jian; Yin, Zijing; Hao, Zhiming; Xiaohong, LV; Pu, Dan
Abstract : Background: Conflicting evidence exists regarding the proportion and function of CD4 + CD25 + Foxp3 + Treg Cells in the peripheral blood (PB) of patients with rheumatoid arthritis (RA) 1-6 . Objectives: The aim of our study was to determine whether Treg cells are defective in Chinese RA patients. Methods: Levels of CD4 + CD25 + Foxp3 + Treg cells in the peripheral blood of 224 patients with RA and 38 healthy controls were detected by flow cytometry. The expression of CTLA-4, GITR, Helios and ICOS was also evaluated in order to gain insight into the regulatory function of Treg cells. The production of IFN-γ, IL17 and IL10 cytokines by Treg cells was also evaluated. Clinical parameters, including DAS28_ESR, the levels of serum Anti-CCP, IgG and IgM were tested. Correlations with Treg cells were systematically analyzed. Results: Compared to the healthy controls, active RA patients had significantly higher frequency of CD4 + CD25 + Foxp3 + Treg cells ( P < 0.01). Furthermore, the CD4 + CD25 + Foxp3 + Treg cells expressed lower CTLA4 ( P < 0.01) and produced higher IL17 ( P < 0.05) and lower IL10 ( P < 0.05) in RA patients compared with healthy controls in vitro stimulation assay. We also found the proportions of CD4 + CD25 + Foxp3 + Treg cells were significantly higher in Anti-CCP + patients compared Anti-CCP - patients ( P < 0.01). The frequency of CD4 + CD25 + Foxp3 + Treg cells in RA patients was positively correlated with DAS28_ESR( r = 0.135, P = 0.043), the levels of serum Anti-CCP( r = 0.239, P < 0.001), IgG( r = 0.239, P < 0.001) and IgM( r = 0.168, P = 0.015). Conclusion: We showed higher frequency of CD4 + CD25 + Foxp3 + Treg cells in PB of RA patients, of which the suppressive capacity was defective. References: [1] Vitales-Noyola M, Layseca-Espinosa E, Baranda L, et al. Analysis of Sodium Chloride Intake and Treg/Th17 Lymphocytes in Healthy Individuals and Patients with Rheumatoid Arthritis or Systemic Lupus Erythematosus. Journal of immunology research 2018; 2018: 9627806. [2] Han GM, O'Neil-Andersen NJ, Zurier RB, et al. CD4+CD25high T cell numbers are enriched in the peripheral blood of patients with rheumatoid arthritis. Cellular immunology2008; 253: 92-101. [3] van Amelsfort JM, Jacobs KM, Bijlsma JW, et al. CD4(+)CD25(+) regulatory T cells in rheumatoid arthritis: differences in the presence, phenotype, and function between peripheral blood and synovial fluid. Arthritis and rheumatism2004; 50: 2775-2785. [4] Furuzawa-Carballeda J, Lima G, Jakez-Ocampo J, et al. Indoleamine 2, 3-dioxygenase-expressing peripheral cells in rheumatoid arthritis and systemic lupus erythematosus: a cross-sectional study. European journal of clinical investigation2011; 41: 1037-1046. [5] Kailashiya V, Singh U, Rana R, et al. Regulatory T Cells and Their Association with Serum Markers and Symptoms in Systemic Lupus Erythematosus and Rheumatoid Arthritis. Immunol Invest2018: 1-15. [6] Naciute M, Maciunaite G, Mieliauskaite D, et al. Increased Numbers of CD4(+)CD25(+) and CD8(+)CD25(+) T-Cells in Peripheral Blood of Patients with Rheumatoid Arthritis with Parvovirus B19 Infection. In vivo2017; 31: 181-185. Disclosure of Interests: None declared